Comparison of Early Oral Feeding With Traditional Oral Feeding After Total Gastrectomy for Gastric Cancer: A Propensity Score Matching Analysis - Wang, Juan; Yang, Min; Wang, Quan; Ji, Gang (Frontiers in Oncology, 2019)
Background: The present study aimed to compare the feasibility and safety of early oral feeding (EOF) with traditional oral feeding after radical total gastrectomy for gastric cancer. Methods: This retrospective study included consecutive patients who underwent total gastrectomy from April 2016 and November 2018. These patients were divided into two groups, according to their postoperative feeding protocol: EOF group (n=314) and traditional oral feeding (TOF) group (n=433). Propensity score matching was used to balance the potential confounders, and 276 patients were selected from each group. The EOF group received oral diet on postoperative day one, while the TOF group were started on oral feeding after the passage of flatus. Results: No significant differences were found in the postoperative complications (P=0.426) and tolerance to oral feeding (P>0.056) between the two groups. The changes in perioperative nutritional markers were also similar between the two groups (P>0.05). The time to first passage of flatus or defecation (47.19 ± 12.00 hours vs. 58.19 ± 9.89 hours, P<0.0001) and length of postoperative hospital stay (6.84 ± 2.31 days vs. 7.72 ± 2.86 days, P<0.0001) were significantly lower in the EOF group compared to the TOF group. Conclusion: EOF may be safe and feasible after radical total gastrectomy with faster recovery and no increased risk of postoperative complications.